Linking life table and predation rate for evaluating temperature effects on Orius strigicollis for the biological control of Frankliniella occidentalis - Ren, Xiaoyun; Li, Xiaowei; Huang, Jun; Zhang, Zhijun; Hafeez, Muhammad; Zhang, Jinming; Chen, Limin; Zhou, Shuxing; Zhang, Lisheng; Lu, Yaobin (Frontiers in Sustainable Food Systems, 2022)
Introduction Orius spp. are generalist predators released in horticultural and agricultural systems to control thrips. Understanding the effects of temperature on the development, predation rate, and population dynamics of Orius is essential for identifying the optimal timing of Orius release for establishing an adequate population to facilitate synchrony with thrips population growth and to prevent thrips outbreaks. The biological control efficiency of natural enemies as well as predator–prey relationships can be precisely described by integrating life table parameters and the predation rate. Methods In this study, the demographic features of Orius strigicollis fed on 2nd instar nymphs of western flower thrips (WFT), Frankliniella occidentalis, were compared at 18.5, 23.5, 27, and 33°C using the TWOSEX-MSChart program. The CONSUME-MSChart program was used to examine predation rates under different temperatures (18.5, 23.5, and 27°C). Results The results showed no significant difference in fecundity among those reared at 18.5, 23.5, and 27°C, but fecundity at these temperatures was significantly higher than that at 33°C. The intrinsic rate of increase (r), finite rate of increase (λ), and net reproduction rate (R0) were the highest at 27°C. The net predation rate (C0) and transformation rate (Qp) were significantly higher at 18.5°C (C0 = 168.39 prey/predator, Qp = 8.22) and 23.5°C (C0 = 140.49 prey/predator, Qp = 6.03) than at 27°C (C0 = 138.39 prey/predator, Qp= 3.81); however, the finite predation rate (ω) showed the opposite trend. In addition to temperature, the stage of O. strigicollis at release can affect population dynamics. Discussion Our study showed that temperature influenced the demographic traits and predation rates of O. strigicollis. When planning a release, the stage of O. strigicollis and temperature should be taken into account to establish an adequate population for the control of WFT.